PENGARUH PENGGUNAAN E-COMMERCE DALAM MENINGKATKAN PENJUALAN USAHA MIKRO KECIL DI KOTA KISARAN - Rut Stefani Br Tambunan; Audrey M. Siahaan; Bonifasius H. Tambunan (PERFORMANCE: Jurnal Bisnis & Akuntansi, 2026)
This study examines the effect of e-commerce usage on increasing sales of Micro and Small Enterprises (MSEs) in Kisaran City. The research is motivated by the shift in consumer behavior toward digital platforms, which challenges conventional sales methods and limits market reach. A quantitative approach was employed using primary data collected through structured questionnaires distributed to 40 MSE actors selected through purposive sampling. The data were analyzed using simple linear regression to evaluate the relationship between e-commerce utilization and sales performance.The findings reveal that e-commerce usage has a positive and significant effect on sales improvement. This is supported by statistical results showing a t-value of 4.591 with a significance level of 0.000, indicating strong evidence to accept the hypothesis . The adoption of e-commerce enables businesses to expand market reach, increase transaction efficiency, and improve customer access, leading to higher sales volume and revenue. However, the study also identifies challenges related to limited digital literacy among business actors.In conclusion, e-commerce serves as an effective strategic tool for enhancing MSE sales performance in Kisaran City, although continuous support and digital capability development are required for optimal utilization.